Pengaruh Rasio I/D terhadap Permulaan Flooding dan Fluktuasi Voltase Sinyal Tekanan Rezim Flooding pada Geometri Kompleks - Astyanto, Achilleus Hermawan; Rahman, Yusuf; Medha, Akbar Yuga Adhikara; Deendarlianto, Deendarlianto; Indarto, Indarto (Jurnal Rekayasa Mesin, 2021)
A nuclear power plant operation requires reliability safety systems. Therefore, an accidental scenario such as the LOCA becomes a specific attention. This relates to a countercurrent flow phenomenon which permits the occurrence of a flooding regime. This study aims to investigate the effets of I/D ratios of the riser on the onset of flooding and time-series voltage fluctuations of differential pressure signals of the flooding regime on a complex geometry representing a PWR hot leg. The test section contains a combination of a horizontal, an elbow and an inclined pipes. Three I/D ratios containing 1.9 (R1), 3.9 (R2) and 8.3 (R3) were assesed. The tabulated data are expressed in the term of a flooding curve. Meanwhile, the statistical features of the time-series voltage fluctuations of the signals are presented on both PDF and PSD graphs. The results obtained show that the assesed I/D ratios do not conduct significance effects on the onset of flooding. On the other hand, there are trends which can be obtained from the time-series signals with the increase of the I/D ratio. Those trends can also be observed in the such statistical features; the PDF and PSD graphs, respectively.